A Case of Nonsyndromic Craniosynostosis in an Infant Child of Jehovah's Witness Parents: Is Surgical Correction Appropriate?. (March 2023) - Linkugel, Andrew D.; Yu, Jennifer; Kopar, Piroska K.; Kodner, Ira J.; Brown, Douglas; Patel, Kamlesh B.
An infant with nonsyndromic craniosynostosis is brought to clinic by his Jehovah's Witness parents to discuss treatment. Five potential courses of action are discussed in the context of biomedical ethics principles. The potential conflict between parents' autonomy to make decisions for their child and the surgeon's ethical duty of beneficence to the patient is explored.